Solidarity and HIV Testing Willingness During the COVID-19 Epidemic: A Study Among Men Who Have Sex With Men in China - Lyu, Hang; Zhou, Yi; Dai, Wencan; Zhen, Shihan; Huang, Shanzi; Zhou, Lanlan; Huang, Liqun; Tang, Weiming (Frontiers in Public Health, 2021)
Background: Solidarity, such as community connectedness and social cohesion, may be useful in improving HIV testing uptake among men who have sex with men (MSM). This study aims to evaluate the impact of solidarity on HIV testing before the coronavirus disease 2019 (COVID-19) and the HIV testing willingness during the COVID-19 among MSM in China. Material and Methods: An online survey was conducted to collect sociodemographic, sexual behavioral and solidarity items information from the participants. We first used factor analysis to reveal the principal component of the solidarity items; then used logistic regression to study the impact of solidarity on HIV testing, by adjusting the possible confounding factors, such as age, education, et al. Results: Social cohesion and community connectedness were revealed by factor analysis. MSM with high community connectedness were more willing to undergo HIV testing before the epidemic adjusted by age (OR: 1.07, 95% CI: 1.01-1.13). The community connectedness was also related to the willingness of HIV testing during the epidemic, with adjusted of 1.09 (95% CI: 1.03-1.15). People who didn’t tested the HIV before the COVID-19 epidemic were more willing to have the HIV testing during the epidemic, which was correlated with the community connectedness, and the OR value was 1.14 (95%: 1.03-1.25). Conclusions: A high level of community connectedness helps to increase the HIV testing rate before the COVID-19 and the willingness of HIV testing during the epidemic among MSM. Strategies that can strength the role of the community in the management and service of MSM.